1996
DOI: 10.1172/jci118736
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aquaporin-2 protein contribute to the urine concentrating defect in rats fed a low-protein diet.

Abstract: Low-protein diets cause a urinary concentrating defect in rats and humans. Previously, we showed that feeding rats a low (8%) protein diet induces a change in urea transport in initial inner medullary collecting ducts (IMCDs) which could contribute to the concentrating defect. Now, we test whether decreased osmotic water permeability (P f ) contributes to the concentrating defect by measuring P f in perfused initial and terminal IMCDs from rats fed 18 or 8% protein for 2 wk. In terminal IMCDs, arginine vasopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 45 publications
1
39
0
2
Order By: Relevance
“…Urea, along with sodium chloride, constitutes a large portion of the medullary hyperosmolar driving force for water transport; therefore, diminished protein intake as reflected by decreased urinary urea excretion could contribute to the concentrating defect in hypothyroidism. In this regard, protein restriction has been shown to decrease maximal urinary concentration (16). In preliminary studies, we observed a decreased intake of protein and calories in the hypothyroid rats.…”
Section: Discussionmentioning
confidence: 57%
“…Urea, along with sodium chloride, constitutes a large portion of the medullary hyperosmolar driving force for water transport; therefore, diminished protein intake as reflected by decreased urinary urea excretion could contribute to the concentrating defect in hypothyroidism. In this regard, protein restriction has been shown to decrease maximal urinary concentration (16). In preliminary studies, we observed a decreased intake of protein and calories in the hypothyroid rats.…”
Section: Discussionmentioning
confidence: 57%
“…To preserve urea delivery to the deep IM, the model assumed that CD urea permeability was low throughout the OM and the initial 1/5 of the IM (3 ϫ 10 Ϫ6 cm/s), which is not inconsistent with low urea permeability values reported in microperfusion studies (36) or those used in mathematical models of the CD (43,44), although our values may correspond to the lower limit. To study the impact of a slightly higher, but still low, OM and early IMCD urea permeability, we conducted a simulation in which CD urea permeability was set to 1 ϫ 10 Ϫ5 cm/s in the OM and in the initial one-fifth of the IM.…”
Section: Urea Permeabilitymentioning
confidence: 86%
“…There is also multiple, but mechanistically unexplained, evidence for an AVP-independent regulation of the water permeability of principal cells in the intact animal (30). Decreased AQP2 expression without changes in AVP or cAMP levels was observed in fasting and protein-deprived rats and humans (1,35). Water deprivation increased AQP2 expression in rats chronically given V 2 R antagonists (24), indicating that the effect of water deprivation on AQP2 expression is not solely due to AVP-elicited cAMP accumulation.…”
Section: Discussionmentioning
confidence: 99%